The Effect of Work Motivation and Job Satisfaction on Service Quality Among Employees of the Bulili Community Health Center, Palu City - Lovita , Sherly; Natsir, Syahir; Wahyuni Adda, Harnida; Ega Nugraha, Mohammad (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effect of work motivation and job satisfaction on service quality at the Bulili Community Health Center, Palu City. The research addresses issues related to suboptimal service quality influenced by human resource factors. A quantitative approach with multiple linear regression analysis was applied to 83 respondents using questionnaires. The results show that work motivation and job satisfaction have a positive and significant effect, both partially and simultaneously, on service quality. The model explains 33% of the variance in service quality. These findings imply that enhancing employee motivation and job satisfaction is essential to improve service quality in public health services effectively. Keywords: Work Motivation, Job Satisfaction, Service Quality, Public Health Services, Employee Performance, Community Health Center, Human Resource Management